Commuting as a Spatial Feature of International Concern’s Location in a Major City. Example of Poznań - Tobolska, Anna (Bulletin of Geography. Socio-economic Series, 2010)
The study presents the spatial aspects of the location of a branch of an international concern in a major city, viz. in Poznań, in terms of commuting streams, both from the city area, and the surrounding area, as well as their variation in the period 2000-2009. In order to characterise the spatial arrangement of commuting, the study used centrographic measures to analyse the variation of commuting directions and identify the areas of the greatest concentration. Furthermore, it was observed that there was a regular disproportion between the group of employees commuting from the city area, and the group of employees commuting from the region, the latter of which was smaller. It thus seems that an international concern production plant influences the local labour market to a significant extent, displaying the strongest regional impact within the range of 20 km from its location, with the direction of this influence being clearly related to the plant’s location in relation to city borders, which might be linked to better communicational accessibility.